Chemoresistive Gas Sensor based on SiC Thick Film: Possible Distinctive Sensing Properties Between H2S and SO2. (2016) - Gaiardo, A.; Bellutti, P.; Fabbri, B.; Gherardi, S.; Giberti, A.; Guidi, V.; Landini, N.; Malagù, C.; Pepponi, G.; Valt, M.; Zonta, G.
Abstract: Commercially available nanosized powder of silicon carbide (named SiC), was thermally, morphologically and structurally characterized. After that, it was screen-printed onto alumina substrates in order to obtain thick films to be tested as functional material for conductometric gas sensors. Samples were exposed to SO2 and H2 S, gases with high importance in many application fields, with the aim of verifying its capability of distinguishing between them. The characterization highlighted that this semiconductor type is selective for sulphur dioxide (SO2 ), in concentrations within the ppm range. This interesting result was found at high temperatures (600-800°C), useful for harsh environmental, and the measurements proved to be completely free from humidity interference. Applications of such a sensor could span many fields, since SO2 plays an important role in air pollution, industrial processes and wine making monitoring.